Nanotechnology as a Means of Forming Benefits for the Sustainable Development of Ukraine’s Economy - Zerniuk, Olena; Glebova, Alla; Pulina, Tetiana (International Journal of Engineering and Technology, 2018)
The research of modern trends of nanotechnology market development was conducted. The basic prospective directions of introduction of nanotechnologies that influence the vital activity of the society and allow to solve problems in the infrastructure and other branches of economy are determined. It is substantiated that it is in the conditions of the crisis that it is necessary to innovate and stimulate the development of nanotechnologies. They allow to increase the efficiency and rationality of using resources at the level of enterprises and industries. Create competitive advantages and prerequisites for sustainable development.Â